Stillbirth and fetal growth restriction - V. G. Volkov; M. V. Kastor (Акушерство, гинекология и репродукция)
Aim: to estimate the rate of early-onset and late-onset fetal growth restriction (FGR) in stillbirth, identify features of placentaassociated complications and determine respective risk factors of stillbirth (especially at early gestational age).Materials and Methods. There were retrospectively studied 61 stillbirth cases in 2016–2019 that occurred in the III level obstetric hospitals: 32 early (23–31 weeks of gestation) and late (32–39 weeks) cases; 156 live births with 8–10 Apgar scores delivered at 36–41 weeks of gestation used as controls. Quantitative parameters were compared using the mean values and standard deviation; nominal parameters were analyzed using odds ratio (OR) and adjusted OR (aOR) with 95 % confidence interval (CI).Results. More than half of stillbirths are associated with FGR with almost 60 % of early-onset phenotype of this pathology. Both in stillbirths and live births, 2/3 of FGR have extremely low weight (OR = 1.8; 95 % CI = 0.6–6.9); 1/3 of growth restricted fetuses were detected shortly before delivery (OR = 1.3; 95 % CI = 0.7–2.4); 1/4 of pregnancies complicated by placental insufficiency are not associated with FGR (OR = 1.4; 95 % CI = 0.7–2.7). Risk factors of stillbirth in pregnancy complicated by FGR are the early-onset growth restriction phenotype (aOR = 3.2; 95 % CI = 1.0–10.3), maternal age over 28 years (aOR = 6.0; 95 % CI = 1.2–29.4), miscarriages and multiple induced abortions (aOR = 3.6; 95 % CI = 1.1–11.2), non-compliance in regular clinics visiting and correction of threatening conditions (aOR = 10.9; 95 % CI = 1.3–91.6), toxoplasma infection (aOR = 6.0; 95 % CI = 1.5–24.5). Early stillbirth with FGR is associated with an older mother's age (aOR = 5.8; 95 % CI = 1.0–34.4), greater parity (aOR = 3.3; 95 % CI = 1.0–10.4), uterine diseases including endometrial polyps, endometriosis, cervix cervicitis, cervix dysplasia (aOR = 4.0; 95 % CI = 0.9–17.2), diabetes mellitus (aOR = 3.1; 95 % CI = 0.8–13.2) and preeclampsia.Conclusion. The rate of early-onset FGR in stillbirth comprises almost 60 % that is twice higher than in live birth, with the rate of late-onset phenotype being less than 30 %. In late stillbirths the early-onset phenotype also prevails. There are no prominent features for stillbirths with FGR compared to previously known risk factors regardless of hypotrophy. Early vs. late stillbirth with FGR is more associated with gynecological pathologies as well as with diabetes mellitus and preeclampsia.